Primary angiosarcoma of the skull: A rare case report - Chugh, Ashish P. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Angiosarcomas are rare high grade endothelial tumors characterized by rapidly proliferating anaplastic cells derived from blood vessels and lining irregular blood filled spaces. Primary neoplasms of the skull are rare, representing 2.6% of primary neoplasms of bone. Primary malignant neoplasms of the skull are even rarer, accounting for only 0.8% of primary malignant neoplasms of bone. CASE DESCRIPTION: We report a 32-year-old female who presented with right parieto-occipital swelling, which gradually increased in size. Radiology was suggestive of a calvarial soft tissue lesion in the right parieto-occipital region with destruction of the adjacent parieto-occipital bone with intracranial extra-axial extension. Complete surgical excision of the calvarial lesion was done under general anesthesia. Postoperative computed tomography (CT) scan of brain (plain and with contrast) showed complete excision of the tumor mass. Histopathological diagnosis was consistent with ‘an angiosarcoma of the skull’. On immunohistochemistry, the atypical endothelial cells were highlighted by CD34, CD31, and factor VIII-related antigen. The patient received adjuvant radiotherapy to the tumor bed. CONCLUSION: Primary angiosarcoma of the skull is a rare tumor with less than 20 cases reported worldwide till date. The treatment should include complete surgical excision with a wide bony margin followed by adjuvant radiotherapy, which in our case has given a good locoregional control even at the end of 2 years. However, these patients should be followed up with repeated scans yearly to rule out locoregional as well as distant recurrence.